Variations of Business Process Reengineering: The Conceptual Framework for Teak Production Sustainability - Alkaff, Muhammad (Dalwa Islamic Economic Studies: Jurnal Ekonomi Syariah, 2023)
For agroforestry industry, in this case teak production, the most challenge that are faced is the balance of teak production optimization and environmental problem. Because, when the production of timber is increased, and then the environment will be affected. Hence, it is required to be found the better solution in balancing the teak production optimization and environment conservation. By searching any literatures, either empirically or theoretically, this article reveals that business process re-engineering that can be implemented by agroforestry industry in teak production may be consist of five stages, they are identifying, model map, analyzing, improvement the process, and re-engineering. All those process must be completed by the principles in the business process they are clarity (understandable), correctness, relevance, economic efficiency, comparability, systematic design. In which must understood and completed in the business process re-engineering may include process mapping, fail-saving, teamwork, and communication. Hence, when it is implemented in the teak production process, it can deliver the positive outcomes that supported the business sustainability in teak production.